2013
DOI: 10.1038/ismej.2013.151
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel intracellular microbiome hosted in arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal fungi (AMF) are important members of the plant microbiome. They are obligate biotrophs that colonize the roots of most land plants and enhance host nutrient acquisition. Many AMF themselves harbor endobacteria in their hyphae and spores. Two types of endobacteria are known in Glomeromycota: rod-shaped Gram-negative Candidatus Glomeribacter gigasporarum, CaGg, limited in distribution to members of the Gigasporaceae family, and coccoid Mollicutes-related endobacteria, Mre, widely distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 64 publications
5
123
0
Order By: Relevance
“…Confocal and electron microscopy suggest that bacteria are diluted along the intraradical symbiotic mycelium (Bianciotto et al, 1996), while spores (Figure 1) act as a reservoir of these microbial communities (Desirò et al, 2014). This result opens the question of what advantages the endobacterium provides to its fungal host during this phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal and electron microscopy suggest that bacteria are diluted along the intraradical symbiotic mycelium (Bianciotto et al, 1996), while spores (Figure 1) act as a reservoir of these microbial communities (Desirò et al, 2014). This result opens the question of what advantages the endobacterium provides to its fungal host during this phase.…”
Section: Resultsmentioning
confidence: 99%
“…The spores were then crushed with a coverslip, incubated in the dark for at least 5 min, and observed under a Leica (Wetzlar, Germany) TCSSP2 confocal microscope (excitation 488 nm; emission 520 nm) to detect the endobacteria. To perform ultrastructural observations, parallel sets of single spores were processed by high-pressure freezing followed by freeze substitution, as described in Desirò et al (2014). After cutting and counterstaining, thin sections were observed under a transmission electron microscope Philips CM10 (Amsterdam, The Netherlands).…”
Section: Cellular and Physiological Analysesmentioning
confidence: 99%
“…Overall, we generated 22 alignments that together contained 284 sequences representing EHB from our surveys. Our data sets also included 61 EHB sequences identified previously from endophytic Ascomycota (Hoffman and Arnold, 2010), 28 EHB sequences from root-associated Mucoromycotina, Mortierellomycotina, and Glomeromycota (Bianciotto et al, 2003;Partida-Martinez and Hertweck, 2005;Partida-Martinez et al, 2007a;Naumann et al, 2010;Sato et al, 2010;Lackner et al, 2011;Desirò et al, 2014Desirò et al, , 2015, and 470 non-EHB reference sequences from GenBank representing the type or otherwise named strains with greatest homology to our unclassified EHB (Supplementary Table 4). …”
Section: Phylogenetic Reconstructions Of 16s Rrnamentioning
confidence: 99%
“…One example of these microbial symbioses is that between plant-associated fungi and their bacterial endosymbionts (endobacteria, endofungal bacteria, or endohyphal bacteria [EHB]). Recent studies have indicated that EHB are widespread in rhizosphere fungi from diverse fungal phyla (e.g., mycorrhizal and pathogenic fungi from the Basidiomycota, Glomeromycota, and Mucoromycotina [6][7][8][9][10][11][12][13]) and in the highly diverse Ascomycota that infect roots, stems, and leaves as endophytes (14) (class 3 endophytes, sensu [15]). However, functional relationships have been studied for only a few associations, limiting inferences regarding the scope and potential importance of EHB-fungal associations in ecological interactions and human applications (but see references 16 and 17).…”
mentioning
confidence: 99%